The Media Discourse of the Newspaper (El Watan) Towards Social Issues Study in Discourse Analysis - Diab Abdullah, Abdul rahman; Basses, Tahir (ALBAHITH ALALAMI, 2025)
Journalistic discourse is a fertile through which most of the segments of the society interact in all their platforms: intellectual, cultural, social, and various settings between the vital structures of the state; which makes it the link between the groups and segments of the society. The role of discourse, moreover, engages in a vital way by establishing a culture of debate on controversial issues that provided a space in the different visions and differing perceptions on how to formulate the discourse and the magnitude of vocabulary for the diagnosis of these issues. Since there is no system of any community empty of the emergence of issues reflecting the public interest which is necessary is reflected in the context discourse of press especially after promises that call package of reforms at the level of the political system in addition to the atmosphere and the process of providing. Such an atmosphere has provided a kind of margin of freedom for the media men by which the can produce opinions and ideas. Those opinions and ideas, in turn, have created insights and differences in the content of press discourse.